Initial annotations for a critique of Human Enhancement from Bio-hermeneutics - García Echeverri, Jonny Alexander (2022)
At the methodological level, the text is composed of two parts. First, some of the most recent positions in philosophy on nature concerning bioenhancement or human enhancement will be exposed. Subsequently, the proposal known as biohermeneutics or critical hermeneutics will be explained based on Conill’s postulates to show how his approach serves as a support to question some techno-scientific reductionisms well as to criticize the human improvement project of the transhumanism.